The structure of g-digroup actions and representation theory - Rodríguez-Nieto, J.G.; Salazar-Díaz, O.P.; Velásquez, R. (Algebra and Discrete Mathematics, 2021)
The aim of this paper is to propose two possible ways of defining a g-digroup action and a first approximation to representation theory of g-digroups.